Post-breeding density and habitat preferences of the Azores Woodpigeon, Columba palumbus azorica: an inter-island comparison. - Dickens, Megan (2005)
In this study we present a post-breeding estimate of the density of the Azores Woodpigeon, Columba palumbus azorica (Hartert & Ogilvie-Grant, 1905). During August 2003, seven of the nine islands of the Azores were surveyed using line transects and distance sampling. Distance analysis, stratified by the island of Terceira and the other islands combined, gives density estimates of 14.52 birds/km2 on Terceira and 5.14 birds/km2 on the other six islands. This indicates that woodpigeons are more abundant than previously thought. The woodpigeon in the Azores is likely to have recently gone through a period of growth. However, woodpigeon densities in the Azores are still much lower than those in mainland Europe. Populations in the Azores may now be limited by the availability of breeding habitat and over-winter food supply. The present survey highlights that there are strong differences between woodpigeon abundance on the different islands of the archipelago, notably with densities on the island of Terceira being higher than on any of the other islands surveyed. Analyses of habitat preferences and the availability of different habitat types suggest that inter-island habitat differences could be a major cause of variation in woodpigeon density across the archipelago.